Strategic Application of AI Intelligent Algorithm in Network Threat Detection and Defense - Wei, Kuo; Zang, Hengyi; Pan, Yiming; Wang, Guanghui; Shen, Zepeng (Journal of Theory and Practice of Engineering Science, 2024)
With the rapid development of information technology, the network has become the main platform for important activities such as People's Daily life, business and government. However, the issue of network security has increasingly become the focus of attention. The rise of cyber intrusions has threatened the security of individuals, businesses and governments. Therefore, intrusion detection technology has become one of the important components of network security. In this paper, the algorithm technology combined with artificial intelligence is used to realize the application status of network security system intrusion detection and defense. The traditional K-means clustering algorithm has problems such as low efficiency, poor detection accuracy and passive processing in network intrusion behavior detection, such as preprocessing and k value determination. In order to solve the above problems, an improved k-means clustering algorithm network security detection model is adopted, and the detection model experiment is realized with the help of data sets.